Is breech still being delivered vaginally? A comparative study - Dars, Saira; Malik, Safia; Bhurgri, Aijaz (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: This study aimed to find out the frequency of singleton term breech presentation and to complete the fetomaternal outcome between spontaneous vaginal and caesarean delivery. We conducted an observational prospective study to describe neonatal outcome of vagina verses cesarean delivery for term breech presentation. Methods: The study was conducted in department of Gynae and Obs. Unit-1, LUMHS, Jamshoro from 1st January 2011 to 31st December 2012. All those pregnant women who were admitted in the department with singleton of breech for elective LSCS or those who were in establish labor were included after verbal informed consent. Results: Out of 3090 Obstetrical admissions, 86 women were having breech presentation. Study divide into two groups group A - Delivered vaginally and group B - Delivered by C-section. The frequency of term breech presentation was 3% (86 out of 3090 obstetrical admissions). Conclusions: Cesarean section, both, elective and emergency, LSCS is more safe for neonates. Maternal morbidity is comparable in both groups.